Bluetooth Performance Analysis on Device Reminder System Based on Distance Measurement and Received Signal Strength Indicator. - Hammam, Rafiqmia Khairuddin Nur; Isnianto, Hidayat Nur (Department of Electrical Engineering and Informatics, Vocational College, Universitas Gadjah Mada, 2021)
Internet of Things (IoT) is one of technology that is currently being developed and widely applied invarious sectors. That is supported by the development of IoT device infrastructure which is increasingly sophisticatedand modern so its capable to meet various needs in its application. IoT can also be applied as a tool to assist one'sactivities in daily life within scope of a private network which are called Personal Area Network (PAN), one of themas a reminder tool. Reminders can be used to remind a person on an important condition such as stuff that dropbehind. Sometimes a person forgets to put his stuff so it left behind in a place, and it will bring up a risk that is loss ofstuff. To help the problem is required a reminder device that is expected to minimize the risk that may occur. Thisdevice applies a point to point communication consisting of one transmitter module that is Bluetooth Low EnergyAT-09 and one receiver module that is Android smartphone. This reminder device will activate the alarm on Androidsmartphone when both modules are spaced more than 5 meters. Then, from the implementation of this system will doan analysis of quality of service based on the value of Received Signal Strength Indicator (RSSI) and the distancebetween the two modules. Quality of service’s parameters which will analyze is delay and packet loss. Based on testresults, signal strenght value (RSSI) and packet loss parameters are strongly influenced by barricade media, becausewhen both modules are in unobstructed condition they are indicates a stronger signal strength value and few packetloss occurs. While for the delay parameter is influenced by the data rate transfer of bluetooth devices.Keywords : RSSI, Distance, Bluetooth Low Energy, Quality of Service, Reminder